Evaluasi Kualitas Website Terhadap Kepuasan Masyarakat Menggunakan Metode Webqual 4.0 dan Importance Performance Analysis (IPA) (Studi Kasus pada Website disperkim.malangkota.go.id Dinas Perumahan dan Kawasan Permukiman Kota Malang) - Ikrom Septian Hadi; Satrio Hadi Wijoyo; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The purpose of this study to obtain results of the evaluation of website use WebQual disprekim.malangkota.go.id 4.0 and get advice on website disperkim.malangkota.go.id using the guidelines and methods of science. The method used in the evaluation of the Department of Housing and Settlement website Malang was that WebQual 4.0 to 3 dimensions as well as methods lmportance and Performance Analysis (LPA), which consists of a conformance level analysis, gap analysis, and analysis of LPA quadrant. The results of the analysis of the quality of Website Department of Housing and Settlement Region Malang shows that the website has a concordance rate of <100% is equal to 94.53%, means that the Website performance level Department of Housing and Settlement Region Malang is still below the level of interest or not in accordance with user expectations. Average Average value gap (GAP) on the Website of Housing and Settlement Region Malang were negative (<0) is equal to -0.24, the results showed that the level of performance Website Department of Housing and Settlement Region Malang is still lacking and has not met expectations users